Experimental study on joint stiffness with vision-based system and geometric imperfections of temporary member structure - Liu, Cong; He, Lin; Wu, Zhenyu; Yuan, Jian (Journal of Civil Engineering and Management, 2018)
In this paper, tests of plug-pin joints are conducted in order to obtain their mechanical parameters, including semi-rigid property. To solve the difficulties of multi-point displacement measurements for small joints, this investigation proposes a vision-based measurement system based on the principle of binocular stereo vision to improve measurement accuracy. Accurate sub-pixel location is achieved according to a template-matching algorithm based on grayscale. Joint performance, including horizontal bar joint tension and compression, semi-rigidity between horizontal bars and upright rods and bracing tension and compression, is investigated in order to acquire joint failure modes as well as load and displacement (or moment and rotation angle) curves. Through data fitting, multi-linear simplified models are proposed to illustrate the joints’ mechanical performance. This paper also investigates geometric imperfection of temporary member structure with plug-pin joints based on several substructure models and temporary grandstand units using a total station theodolite. The probabilistic models of initial member out-of-straightness and story frame out-of-plumb have been acquired, which can be used into Monte Carlo simulation to create stochastic model of the temporary member structure.